External Knowledge Sourcing and Firm Innovation Efficiency. (29th May 2019) - Asimakopoulos, Grigorios; Revilla, Antonio J.; Slavova, Kremena
Abstract: This study examines the relationship between external knowledge sourcing and firm innovation efficiency. We build on the organizational learning theory to propose that this relationship follows an inverted U‐shape: as the level of external knowledge sourcing increases from low to moderate, firm innovation efficiency increases; as the level of external knowledge sourcing increases from moderate to high, firm innovation efficiency declines. Further, we explore the moderating role of different contextual factors and contend that this inverted U‐shaped relationship is flattened in firms that operate in high‐tech sectors and in firms that face high internal constraints for innovation. Our empirical analysis is based on a sample of 3, 204 Spanish firms over the period 2004–2015, and our results provide support for these contentions. We used data envelopment analysis methodology to estimate firm innovation efficiency relative to industry best performers, and truncated regression models for panel data with bootstrapped confidence intervals to test our hypotheses.